INFLUENCE WORK MEANING AND CONDITIONS WORKER INDIVIDUAL TO INTENTION FOR STAY MEDIATED BY WORK-FAMILY-CONFLICT IN EMPLOYEES IN SERVICE COMPANIES - Salma Sintya; Mohamad Trio Febriyantoro; Zulkifli Zulkifli; Fendi Saputra; Yohanes Totok Suyoto (Asosiasi Dosen Muda Indonesia, 2022)
Research this aim for researching influence profession meaning and condition worker individual to intention for stay mediated by conflict family work for employees in the company field services . Research design this use method study quantitative with Structural Equation Modeling model and using Smartpls.40 software. Data collection techniques using questionnaire with intermediary Google Form, and the number of samples is 124. Research results this showing that profession meaning have influence negative and no significant to work family conflict , work family conflict have influence positive and significant to intention for residence and conditions worker have influence positive and significant to work family conflict on employees in the company field services .